2018
DOI: 10.15566/cjgh.v5i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Long-term Impact of Values-based Community Health Education in Cambodia

Abstract: Introduction: Community Health Education (CHE) is a development strategy which aims to address the needs of communities in developing countries through an emphasis on moral values and civic education. The syllabus of the CHE program guides a trainer to find the needs of a developing community and take a moral values-based approach to health issues such as alcoholism, smoking, injuries to accidents, and sexually-transmitted illnesses. The fundamental philosophy is that of development as opposed to aid. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The study found that community health education improved participants' knowledge of hepatitis B transmission and prevention and encouraged them to get vaccinated against the virus. (Cuttilan, et al 2018) While the literature suggests that community health education can be effective in preventing the spread of hepatitis B and C, there are also studies that have found limited or no impact of community health education on these issues. For example, a study in Turkey found that community health education had limited impact on increasing knowledge and promoting healthy behaviors related to hepatitis B and C.…”
Section: Literature Of Reviewmentioning
confidence: 99%
“…The study found that community health education improved participants' knowledge of hepatitis B transmission and prevention and encouraged them to get vaccinated against the virus. (Cuttilan, et al 2018) While the literature suggests that community health education can be effective in preventing the spread of hepatitis B and C, there are also studies that have found limited or no impact of community health education on these issues. For example, a study in Turkey found that community health education had limited impact on increasing knowledge and promoting healthy behaviors related to hepatitis B and C.…”
Section: Literature Of Reviewmentioning
confidence: 99%